Evaluation of the Usability Learning Management System during the Covid-19 Pandemic Using the Scale System - Roy Inzaqhi Saputra; Wahyu Andhyka Kusuma (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic has made E-learning users rapidly increase; this is due to the government's WFH (work from home) policy so that the entire process of learning activities in class is replaced with online learning models. One of the widely used E-Learning platforms is the UMM Learning Management System, as one of the widely used platforms, of course, it is necessary to evaluate satisfaction so that there will be improvements in the future. System Usability Scale is one of the evaluation methods used to see the usability of a software product. Usability evaluation was carried out to 10 student user respondents across generations. Based on the evaluation of the Usability E-learning platform, UMM's Learning Management System has a score of 82.8 and is considered to have fulfilled the points of usability.